Working Together on Diverse Tasks: A Longitudinal Study on Individual Workload, Presence and Emotional Recognition in Collaborative Virtual Environments - Khojasteh, Negar; Won, Andrea Stevenson (Frontiers in Virtual Reality, 2021)
Numerous studies have shown the potential benefits of collaborative virtual environments (CVEs) for distributed teams. However, there are few longitudinal studies on collaboration in immersive virtual environments, and existing studies mostly examine how pairs or groups adapt over time. In a longitudinal study, we examined what does and does not change over time as individual users adapt to collaboration in virtual environments. In our mixed-methods, exploratory study, we matched 20 participants in random pairs over five sessions. We assigned each participant to complete a different collaborative task, with a different partner, in each session. Our quantitative data analysis and qualitative interview data show that adaptation to VR increased significantly over time. Presence ratings did not show change over time, but participants reported developing new ways to communicate in VR. We also identified patterns indicating a relationship between a person’s emotional state and their partner’s ability to recognize their emotion. We conclude with a discussion of our findings and provide design implications and future directions for designers and researchers in the field.